DEVELOPMENT AND ANALYSIS OF HIGH SPEED DRILLING INDUCED DELAMINATION IN GLASS FIBER REINFORCED POLYMER - WOO , TZE KEONG (2016)
Composite materials are increasingly popular in various fields for its advantages in physical and mechanical properties. However, the wider applications of composite materials have often been hindered due to the difficulty and high cost associated with shaping and machining them into damage free composite parts with requisite tolerances and surface finish. The objectives of this research arc to develop and analyze drilling induced delamination during high speed drilling of glass fiber reinforced polymer (GFRP). The GFRP composite was designed and fabricated with less that 5 % void content using vacuum resin infusion technique with fiber volume fraction higher than 55 %, suitable for structural application.